(untitled) (The Geographic Base, 2024)
Land use and land cover (LULC) is one of the important measures which shows how human activities are changing the environment. These changes reshape earth’s physical surface, and also influence its ecosystem and hydrological process. This study examined LULCC and river sinuosity in the Khageri Sub-Watershed in Chitwan, Nepal. Pre-classified 10-meter Sentinel-2 land use land cover data from ESRI (Environmental Systems Research Institute) was used to create LULC maps for 2017, 2019, 2021, and 2023 in ArcGIS. Standard GIS methods were used for the change detection analysis. Sentinel-2 satellite imagery from the Copernicus Space Data Ecosystem was used to manually digitize river centerlines. River sinuosity was analysed at six segments of the Khageri River for 2017 and 2023. The selection of the study period was based on the availability of consistent, high-resolution, 10-meter Sentinel-2 data for the area. The results showed a clear trend of urbanization and land change, as the built-up areas was increased by 7% and crop and forest areas was declined by 19.60% and 4.19% respectively, from 2017 to 2023. Change in river sinuosity indicated morphological changes that could increase flood risks and influence habitat stability in the area. The results highlight the close relationship between land use changes and river behaviour and thus emphasize the need of integrated watershed management and sustainable development planning.